Using Concept Circles Strategy on Students’ Writing Ability in Descriptive Text - pahmi pahmi; Satriandri Yoskavia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
This research aimed to investigate the concept circles strategy on Students’ writing ability in descriptive text. The writer conducted pre experimental research. The sample consisted of 29 students. Before giving treatment, the students were given pre-test, and post-test after students were given treatment. The technique of collecting the data was the writing test. The technique of data analysis used paired sample T-test formula in order to find out the significant effect that compares pre-test and post-test score in one class only analyzed by using SPSS 16.0 version. Based on the data analysis, T showed 8.382 compared at significant level 5% (2.05), and at level 1% (2.76). It can be read 2.05<8.382>2.76. Therefore, there is a significant effect of using Concept Circles Strategy at Darul Hikmah Islamic Senior High School Pekanbaru.